Анализ пространственно-временной изменчивости показателя заповедности территории регионов Украины с использованием геоинформационных технологий - Волков, А.И.; Попик, О.В. (Культура народов Причерноморья, 2013)
Сформирована база данных, характеризующая состояние природно-заповедного фонда
Украины за период 2000-2012 гг. Рассчитан показатель заповедности и проанализирована динамика его
изменения. Построены тематические карты, представляющие пространственное распределение
показателя заповедности по территории Украины. Выделены области, наиболее подходящие для
зеленого и экологического туризма. Сформований банк даних, що характеризує стан природно-заповідного фонду України за
період 2000-2012 рр. Розрахований показник заповідності і проаналізована динаміка його змінення.
Отримані тематичні карти, що представляють просторовий розподіл показника заповідності за
територією України. Виділені області, що найбільш відповідають вимогам для організації зеленого та
екологічного туризму. Geographical location of Ukraine is characterized by complex favorable environmental conditions:
climate, recreational resources, unique natural landscapes etc., which are very appropriate to expand reserve
areas within the country. The development of natural reserve fond in Ukraine is a complex procedure which is
needed to be described from different points of view.
The goal of the research is to analyze the spatial and time variability of natural reserve index for regions of
Ukraine and development of up-to-date database which contains characteristics of Ukrainian reserve objects.
Natural reserve index shows ratio between area of reserves and general area of territory in question. Research
shows that the higher value of natural reserve index corresponds to Hmelnitskaya region end equals to 12,68%
the lowest values of the index correspond to Lvovskaya, Luganskaya, Kharkivskaya, Ternopolskaya,
Chernigovskaya, Nikolaevskaya, Gitomirskaya, Poltavskaya, Vinnitskaya, Sumskaya, Kirovogradskaya regions.
In general the maximal values of the index correspond to the western and southern parts of Ukraine and the
minimal values correspond to northern, eastern, central parts that can be explained by irregular distribution of
industrial objects, recreational and climatic resources etc.
Development of the database of reserve natural areas using of geographic information technologies is a very
helpful tool which simplifies access to appropriate data. Zoning of territory by the natural reserve index should
be utilized in order to improve land use and environment management.